THE ROLE OF FARMERS IN THE ECONOMY AND PROSPECTS FOR THEIR DEVELOPMENT IN UZBEKISTAN - Narinbayeva Gulnora Karimovna; Jalilov Shoxjahon Kholbozor Ogli; Mirzaev Musurmon Umidullayevich; Khaitbayeva Dilobar Zahidovna (Journals Park Publishing, 2022)
The article covers the role of peasant farms in the economy and prospects of their development in Uzbekistan. Peasant farms play an important role in solving the food problem.
Keywords: peasant farms; food industry; product